2020
DOI: 10.3390/ma13153269
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Indicators and an Analytic Method for Moisture Susceptibility and Rutting Resistance Evaluation Using a Hamburg Wheel Tracking Test

Abstract: The Hamburg wheel tracking test (HWTT) is widely used to evaluate the performance of asphalt mixtures. According to HWTT specifications, the stripping inflection point (SIP) and the rut depth at a certain number of load cycles are two common indicators for evaluating the moisture susceptibility and rutting resistance of asphalt mixtures, respectively. Although these indicators have been used extensively by several transportation institutions, the reliability and stability in evaluating asphalt mixture behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In order to avoid this defect, Tsai and Harvey (2003) put forward the threestage Weibull approach to fit rut curve. Based on this, Yin et al (2014) proposed a new method to evaluate the performance of water stability and high-temperature performance by fitting the whole rutting process and proved the reliability of evaluation parameters. In this paper, the Yin fitting method is used to analyze the test results.…”
Section: Evaluation Parameter and Analysis Methodsmentioning
confidence: 99%
“…In order to avoid this defect, Tsai and Harvey (2003) put forward the threestage Weibull approach to fit rut curve. Based on this, Yin et al (2014) proposed a new method to evaluate the performance of water stability and high-temperature performance by fitting the whole rutting process and proved the reliability of evaluation parameters. In this paper, the Yin fitting method is used to analyze the test results.…”
Section: Evaluation Parameter and Analysis Methodsmentioning
confidence: 99%
“…Another problem of the AASHTO procedure is the use of a straight line to represent stripping deformation. It is known that stripping deformation increases nonlinearly as the loading cycle increases (3)(4)(5)(6)(7). Drawing a straight line through these points can cause an error in the analysis.…”
Section: Graphical Methods (Aashto Method)mentioning
confidence: 99%
“…Finally, the cumulative rut depth versus loading cycle (or wheel pass, 1 cycle = 1 wheel pass) is plotted to evaluate the rutting and stripping performance of the tested sample. The typical HWTT plot usually has three distinct phases: post-compaction phase, creep phase, and stripping phase (3)(4)(5)(6)(7). The densification of the specimen under the wheel load in the earlier stage of loading is attributed to the post-compaction phase.…”
mentioning
confidence: 99%
“…Two groups of laboratory methods are most often used to assess the rutting resistance of asphalt mixtures. The first group includes methods of testing a single layer [ 25 , 26 , 27 ], while the second group of methods enables the testing of a set of pavement construction layers [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of rutting resistance tests carried out in many research centers, it was found that the content, type and quality of the binder used for asphalt mixtures production have a significant impact on their rutting resistance [ 24 , 25 , 26 , 27 ]. The literature describes many methods of binder modifications, including polymers, hydrated lime and basalt fibers, polyalphaolefins, CR, synthetic wax and cellulose fibers [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%